Belly Dancers Syndrome: a diagnostic challenge - Moreira,Ana Raquel (2017)
Introduction: Belly Dancers syndrome is a rare movement disorder characterized by involuntary contractions of the diaphragm, causing abnormal movements in the abdominal wall. Many different causes were described such as trauma, infections, metabolic disorders and drug ingestion. Sometimes the cause remains uncertain and a psychogenic disturb has been suggested in others. Case report: A 14-year-old female presented with episodic involuntary movements of the abdomen that had started one week after falling. Besides these abnormal movements, physical examination was unremarkable. Belly Dancers syndrome was suspected and the neuroimaging revealed C3 and C4 nerve root injuries and several vertebral lesions. The treatment performed included oral chlorpromazine, immobilization with Jewett vest, rest and physiotherapy, with remarkable symptoms improvement. Discussion: This clinical presentation of this syndrome is quite unusual, which may lead to late diagnosis or ineffective treatments. We report a case of traumatic Belly Dancers syndrome that improved significantly with stabilization of the lesion.